2005
DOI: 10.1002/ijc.21081
|View full text |Cite
|
Sign up to set email alerts
|

Interventional study in 1,232 young German children to prevent the development of melanocytic nevi failed to change sun exposure and sun protective behavior

Abstract: Sunscreens have been proposed as protective measures to inhibit the development of melanocytic nevi in childhood and to decrease the long term risk for cutaneous melanoma development. Our present study investigates the influence of sunscreen use and education on the number of incident melanocytic nevi. A total of 1,812 children in 78 public nursery schools in 2 German cities were randomized to 3 study arms: (i) parents were informed on study purpose and sun protection measures only at an initial educational me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 55 publications
0
66
0
1
Order By: Relevance
“…25 The German trial failed to change patterns of sunscreen use between the randomization groups because apparently, sunscreen use was already highly prevalent in all groups at study start. 26 The Vancouver trial reported estimations of the total amounts of time spent in the sun during the 3-year trial duration but did not report duration of sun exposure per day with or without sunscreen use.…”
Section: 19mentioning
confidence: 99%
See 1 more Smart Citation
“…25 The German trial failed to change patterns of sunscreen use between the randomization groups because apparently, sunscreen use was already highly prevalent in all groups at study start. 26 The Vancouver trial reported estimations of the total amounts of time spent in the sun during the 3-year trial duration but did not report duration of sun exposure per day with or without sunscreen use.…”
Section: 19mentioning
confidence: 99%
“…25,26 The Vancouver trial in Canada found a reduction in the development of new nevi in children with dense facial freckling and found no effect in children without dense facial freckling. 25 The German trial failed to change patterns of sunscreen use between the randomization groups because apparently, sunscreen use was already highly prevalent in all groups at study start.…”
Section: 19mentioning
confidence: 99%
“…This systematic review evaluated five research articles chosen according to the study criteria (Table 1) [29][30][31][32][33] . The results obtained from the studies were grouped under the headings of "Research groups and characteristics", "Characteristics of program applied", "Evaluation of program applied", "Results obtained", and "Methodological quality of the studies", all of which are described in greater detail below.…”
Section: Resultsmentioning
confidence: 99%
“…All the studies were RCTs conducted between 1995 and 2007, with four being carried out in the United States of America 9,30,32,33 and one in Germany 31 . Regarding the samples of the studies included in the research, two consisted of children 29,31 one of parents 32 , and one of preschool personnel 33 , parents, and school principals 30 .…”
Section: Research Groups and Characteristicsmentioning
confidence: 99%
“…Bauer et al (11) reported an interventional study to decrease the incidence of melanocytic nevi in 1232 German children. The authors investigated the efficacy of education and free sunscreen on decreasing the incidence of melanocytic nevi three years following their intervention.…”
Section: Discussionmentioning
confidence: 99%